2018
DOI: 10.1176/appi.ps.201700224
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Psychiatric Inpatients at the Veterans Health Administration

Abstract: Although patient safety events in VHA psychiatric inpatient units were relatively common, a great majority of these events resulted in little or no patient harm. Nevertheless, many were preventable, and the study provides data with which to target future initiatives that may improve the safety of this vulnerable patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 39 publications
3
31
2
Order By: Relevance
“…This equates to approximately 8% of the patients treated in the hospital. This level of AEs is consistent with some studies 23,27 while a more recent study reported approximately 20% patients experienced a patient safety event 28,37 .…”
Section: Statement Of the Principal Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…This equates to approximately 8% of the patients treated in the hospital. This level of AEs is consistent with some studies 23,27 while a more recent study reported approximately 20% patients experienced a patient safety event 28,37 .…”
Section: Statement Of the Principal Findingssupporting
confidence: 91%
“…In Marcus`s survey 37 the most frequent events were medication errors (delayed and missed doses, 17.2%), followed by adverse drug events (4.1%), falls (2.8%), and assaults (1.0%). Most reported patient safety events (94.9%) resulted in little or no harm although more than half of the events (56.6%) were deemed preventable 37 .…”
Section: Statement Of the Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 7 studies, no factors were identified [31,34,50,58,65,78,81] and in two, it was unclear [44]. Most studies reporting factors, discussed multiple individual factors (range = 1-7, average = 2.3) across multiple domains (range = 1-4, average = 2.0).…”
Section: Description Of Contributory/associated Factorsmentioning
confidence: 99%
“…A previous safety study reported that severely mentally ill patients admitted to medical-surgical wards experienced a mean number of almost six AEs per hospitalization (Daumit et al, 2016). A first study into safety of hospitalized psychiatric patients reported that approximately one in five patients experienced a patient safety event (AEs or medical errors) (Marcus, Hermann, Frankel, & Cullen, 2017). To our knowledge, a study evaluating process and outcome indicators of psychiatric inpatient care for patients with psychosis is lacking.…”
Section: Introductionmentioning
confidence: 99%